2014
DOI: 10.1159/000362165
|View full text |Cite
|
Sign up to set email alerts
|

MRI Study: Objective Olfactory Function and CNS Pathologies in Patients with Multiple Sclerosis

Abstract: Background: Multiple sclerosis (MS) is a chronic disease characterized by CNS lesions causing physical and cognitive impairment. Using psychophysical testing, an olfactory disorder is diagnosed in 15-38.5% of patients with MS. Olfactometry permits objective testing of the sensory nerve function. Methods: The study looked at 20 patients with MS. Clinical, olfactory (chemosensory evoked potentials), and MRI data (volume of the bulbus olfactorius (BO), olfactory brain (OB), lesions in the CNS) were analyzed. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…The extent of OEP disturbance in MS related to poor performance on the UPSIT score and to the extent of physical disability, as measured by Expanded Disability Status Score (EDSS), in the disease (see clinical association section below) 22 38. Other independent groups have corroborated these OEP findings in MS, adding further credence to physiological disturbance of these olfactory structures at some point in the clinical evolution of the disease 29 31 39…”
Section: Olfactory Dysfunction In Cns Demyelinating Diseasesmentioning
confidence: 92%
See 4 more Smart Citations
“…The extent of OEP disturbance in MS related to poor performance on the UPSIT score and to the extent of physical disability, as measured by Expanded Disability Status Score (EDSS), in the disease (see clinical association section below) 22 38. Other independent groups have corroborated these OEP findings in MS, adding further credence to physiological disturbance of these olfactory structures at some point in the clinical evolution of the disease 29 31 39…”
Section: Olfactory Dysfunction In Cns Demyelinating Diseasesmentioning
confidence: 92%
“…Through the measurement of olfactory bulb and tract volume, a Berlin-based group have repeatedly demonstrated reductions in these structures in MS compared with controls,37 39 49 and have shown that these changes relate to loss of smell and37 49 OEP disturbance (figure 1C) 39. Olfactory bulb volume and olfactory sulcus depth have also been shown to be inversely correlated with disease duration and attack frequency in MS 54.…”
Section: Olfactory Dysfunction In Cns Demyelinating Diseasesmentioning
confidence: 97%
See 3 more Smart Citations